Productivity and employment effects of digital complementarities - María Teresa Ballestar; Ester Cami\~na; Ángel Díaz-Chao; Joan Torrent-Sellens (Journal of Innovation & Knowledge (JIK), 2021)
Modern economic growth is no longer found in total factor productivity (TFP) because there are gains from technological change that are never recorded in the returns from innovation or in the National Accounts. The existence of complementarities among technologies derived from the use of robotics, electronic commerce, or innovation is difficult to assess through country-level records. Because the literature has mainly focused on robotisation at an aggregate or industry level, research focusing on a firm level and complementarities analysis have been limited. To fill the gap, in this paper, we intend to provide new evidence regarding the effects of robotisation, digitisation, and innovation on productivity and employment in firms, by using a large sample of 5511 Spanish manufacturing firms for the period 1991-2016. This data captures the payoff to the high rates of investment necessary to upgrade the production technology for firms in a new globally competitive framework.
Keywords: J23; J24; 650; Robotisation; Productivity digitalisation